TANTANGAN DAN PELUANG SMK NEGERI JAGOI BABANG MENGEMBANGKAN SPIRIT KEWIRAUSAHAAN KEARIFAN LOKAL BIDAI PERBATASAN MALAYSIA INDONESIA KABUPATEN BENGKAYANG - Asriati, Nuraini; Wardani, Sandra Fitria (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The Indonesia-Malaysia border region has the potential for various natural and cultural resources. The development of entrepreneurial skills is critical, particularly for the younger generation, in order to improve the economic potential of the region near the Indonesia-Malaysia border. This study intends to examine the obstacles and opportunities experienced by students in fostering the entrepreneurial spirit of Bidai indigenous wisdom in Bengkayang Regency, Malaysia-Indonesia border. The qualitative research method was applied in this study. Data was gathered through conversations with students who had prior experience creating Bidai local wisdom entrepreneurial firms. Data analysis employs interactive data analysis techniques such as data reduction, data visualization, and conclusion or verification stages. According to the findings of the study, the problems that students encounter include a lack of funding to start a business, a lack of entrepreneurial knowledge and skills, and competition from imported products. Opportunities include the opportunity for cross-border markets with Malaysia, which expands opportunities for indigenous knowledge goods, as well as government and related organization support. This study's recommendations include enhancing students' entrepreneurial knowledge and skills, government assistance in getting financing and training, building effective marketing tactics, and forming partnerships with connected parties